Hubungan Antara Keseimbangan Dan Kelincahan Dengan Kemampuan Dribble Bola Basket Pada Siswa Kelas 11 Putra Di SMA Negeri 1 Bululawang - Naufalin Nafisah; Eko Hariyanto (Jurnal Bintang Pendidikan Indonesia, 2024)
Dribble is one of the basic techniques in the game of basketball by bouncing the ball on the floor, with the aim of scoring. To dribble well, several components are needed, including balance and agility. This research was conducted with the aim of improving students' basic basketball dribbling technical skills, as well as to find out whether there is a relationship between balance and agility and students' basketball dribbling abilities. This research design uses descriptive correlational research with a quantitative approach. Data collection uses balance, agility and dribble test instruments. Data analysis uses descriptive statistics and inferential statistics using the Pearson Product Moment technique and Multiple Linear Regression. From the test results it is known that balance and agility have an influence on dribbling ability by 48,3%, and each component makes a contribution, including the balance component by 21,3% and the agility component by 78,5%. So it can be concluded (1) there is a significant relationship between balance and dribble ability, (2) there is a significant relationship between agility and dribble ability, (3) there is a significant relationship between balance and agility and dribble ability.